Calcium Transients in the Rhabdomeres of Dark- and Light-Adapted Fly Photoreceptor Cells - Oberwinkler, Johannes (J Neurosci, 2000)
The light response of fly photoreceptor cells is modulated by changes in free Ca(2+) concentration. Fly phototransduction and most processes regulating it take place in or very close to the rhabdomere. We therefore measured the kinetics and the absolute values of the free Ca(2+) concentration in the rhabdomere of fly photoreceptor cells in vivo by making use of the natural optics of the fly's eye. We show that Ca(2+) flowing into the rhabdomere after light stimulation of dark-adapted cells causes fast Ca(2+)transients that reach peak values higher than 200 μm in <20 msec. Approximately 500 msec later, the free Ca(2+) concentration has declined again to ∼20 μm. The duration of the Ca(2+)transients becomes still shorter, and their size reduced, when the photoreceptor cell is light-adapted. This reduction in duration and size of the Ca(2+) transients is graded with the intensity of the adapting light. The kinetics and absolute values of the free calcium concentration found to occur in the rhabdomere are suitable to mediate the fast feedback signals known to act on the fly phototransduction cascade.